Psychology and sociology analysis of eating disorder factors among athletes: age-based perspectives - Sidik, Mochammad Rasyid; Fitri, Mustika; Paramitha, Sandey Tantra; Apriady, Hilmy (JETL (Journal of Education, Teaching and Learning), 2024)
Eating disorders are prevalent among athletes, impacting their physical and psychological health. This study examines the influence of psychosocial factors—specifically stress and social support—on eating disorders among senior and junior athletes. A descriptive quantitative approach was used, with taekwondo athletes from SLOMPN UPI and the West Java Taekwondo Team selected through purposive sampling. Data were collected using three validated questionnaires: the Eating Disorder Screen for Athletes (EDS-A), the Perceived Stress Scale (PSS), and the Athletes Received Support Questionnaire. Statistical analysis, including Two-Way ANOVA and descriptive statistics, was performed using IBM SPSS Statistics Version 25. Results showed a significant impact of psychosocial factors on eating disorders for both senior and junior athletes (p < 0.05). Senior athletes exhibited higher mean scores for eating disorders (20.53), stress (33.62), and social support (70.14) compared to junior athletes, who had mean scores of 18.94, 28.91, and 64, respectively. Despite receiving more social support, senior athletes experienced higher stress levels, which correlated with a greater risk of eating disorders. Conversely, junior athletes with lower stress levels showed a reduced risk of eating disorders, highlighting the importance of strong social support networks. These findings suggest that interventions should focus on enhancing social support and stress management tailored to different age groups. Future research should explore gender differences in psychosocial factors affecting eating disorders to develop more targeted interventions.